UJI AKTIVITAS ANTIBAKTERI INFUSA DAUN SIRIH (Piper betle L.) TERHADAP BAKTERI Escherichia coli - Hasyrul Hamzah; Amrina Rossada Septilapani; Neni Frimayanti (Jurnal Penelitian Farmasi Indonesia, 2021)
Research has been carried out on the antibacterial activity test of betel leaf infusion against Escherichia coli bacteria by solid dilution method. This study aims to determine the antibacterial activity of betel leaf infusion (Piper betle L.) against Escherichia coli bacteria. Bacterial control used a bacterial suspension dilution of 10-5 with a colony count of 212.33 colonies/mL and the control media showed that the media used was free from contamination. The results of the antibacterial research showed that the infusion of betel leaf had activity in inhibiting the growth of Escherichia coli bacteria at an infusion concentration of 25% with the number of colonies 188.33 colonies/mL, 50% with the number of colonies 160.66 colonies/mL, 75% with the number of colonies 137, 33 colonies/mL and 100% with the number of colonies 106.33 colonies/mL. The results of data analysis with the percentage decrease in the number of betel leaf infusion colonies against Escherichia coli bacteria that the higher the betel leaf infusion concentration, the less the number of bacterial colony growth, there was a difference marked by the difference in the number of bacterial colonies between control bacteria and the number of bacterial colonies at each concentration infusion.